2020
DOI: 10.1136/bmjopen-2020-039168
|View full text |Cite
|
Sign up to set email alerts
|

Protocol description of the HOVON 141/VISION trial: a prospective, multicentre, randomised phase II trial of ibrutinib plus venetoclax in patients with creatinine clearance ≥30 mL/min who have relapsed or refractory chronic lymphocytic leukaemia (RR-CLL) with or without TP53 aberrations

Abstract: IntroductionLiterature is scarce on the combination treatment of ibrutinib and venetoclax (IV) is scarce in relapsed or refractory chronic lymphocytic leukaemia (RR-CLL). Especially, the possibility of stopping ibrutinib in RR-CLL patients in deep remission is unclear.Methods and analysisIn the HOVON 141/VISION trial, patients with RR-CLL are treated with 12 cycles of IV after a short induction with ibrutinib. Patients reaching undetectable minimal residual disease (uMRD) after 12 cycles of IV are randomised 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…CAPTIVATE study further attested superiority of this combination resulting in the 30-month progression free survival rate of ~95% across all treated patients. Similar data are emerging from many different institutes in large studies ( 28 , 29 ) and also for patients with relapsed/refractory CLL ( 29 , 30 , 60 ). Recent results from the randomized trial of ibrutinib and venetoclax versus chlorambucil and obinutuzumab (CLL GLOW trial) validated the ibrutinib and venetoclax couplet therapy for CLL as a time-limited oral targeted therapy for patients with CLL ( 33 ).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…CAPTIVATE study further attested superiority of this combination resulting in the 30-month progression free survival rate of ~95% across all treated patients. Similar data are emerging from many different institutes in large studies ( 28 , 29 ) and also for patients with relapsed/refractory CLL ( 29 , 30 , 60 ). Recent results from the randomized trial of ibrutinib and venetoclax versus chlorambucil and obinutuzumab (CLL GLOW trial) validated the ibrutinib and venetoclax couplet therapy for CLL as a time-limited oral targeted therapy for patients with CLL ( 33 ).…”
Section: Discussionsupporting
confidence: 73%
“…Ex vivo model that promotes CLL cell proliferation demonstrated that each drug works on different subpopulation resulting in synergy ( 25 ). Both drugs have been used in combination during clinical trials for B-cell malignancies such as mantle-cell lymphoma (MCL) ( 26 ), treatment-naïve CLL ( 18 , 27 , 28 ) or previously treated CLL ( 29 , 30 ). Additional studies are further establishing clinical utility of the combination for CLL cells, namely, defined duration of therapy after achievement of u-MRD status ( 31 , 32 ).…”
Section: Introductionmentioning
confidence: 99%
“…Levin et al, 98 in HOVON 141/VISION trial, are exploring the effects of the combination treatment with ibrutinib+venetoclax in RR/CLL. After a short induction with ibrutinib, patients with RR/CLL are treated with 12 cycles of venetoclax.…”
Section: Inhibiting Bcl-2 With Bh3-mimeticsmentioning
confidence: 99%
“…PFS after 12 months follow-up is to be the primary endpoint of the study, which has not been completed yet. 98 …”
Section: Inhibiting Bcl-2 With Bh3-mimeticsmentioning
confidence: 99%
“…Patients becoming MRD 1 on ibrutinib remain on ibrutinib; if there is progressive disease, these patients will go off protocol. Reinitiating treatment due to MRD 1 is not considered progression if remission is maintained or achieved (please see the published protocol for further details 14 ). We report the preplanned analysis for the first 51 eligible patients reaching cycle 15.…”
mentioning
confidence: 99%